2010
DOI: 10.1002/jnr.22421
|View full text |Cite
|
Sign up to set email alerts
|

Role of adenosine kinase in cochlear development and response to noise

Abstract: Adenosine signalling has an important role in cochlear protection from oxidative stress. In most tissues, intracellular adenosine kinase (ADK) is the primary route of adenosine metabolism and the key regulator of intracellular and extracellular adenosine levels. The present study provides the first evidence for ADK distribution in the adult and developing rat cochlea. In the adult cochlea ADK was localised to the nuclear or perinuclear region of spiral ganglion neurones, lateral wall tissues and epithelial cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
15
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 57 publications
0
15
0
Order By: Relevance
“…Only two studies tested the otoprotective potential of the ADK inhibitor ABT-702. Although ABT-702 failed to restore hearing thresholds after exposure to traumatic noise (Vlajkovic et al, 2010), the chronic treatment with ABT-702 (1.5 mg/kg intraperitoneally twice a week) attenuated hair cell loss and age-related hearing loss in C57BL/6 mice (Vlajkovic et al, 2011). It remains to be determined why ABT-702 had an opposite outcome in those studies.…”
Section: B Applications In Preclinical Studiesmentioning
confidence: 97%
See 3 more Smart Citations
“…Only two studies tested the otoprotective potential of the ADK inhibitor ABT-702. Although ABT-702 failed to restore hearing thresholds after exposure to traumatic noise (Vlajkovic et al, 2010), the chronic treatment with ABT-702 (1.5 mg/kg intraperitoneally twice a week) attenuated hair cell loss and age-related hearing loss in C57BL/6 mice (Vlajkovic et al, 2011). It remains to be determined why ABT-702 had an opposite outcome in those studies.…”
Section: B Applications In Preclinical Studiesmentioning
confidence: 97%
“…Therefore, adenosine metabolic enzymes, such as ADK, have emerged as attractive targets for controlling oxidative stress in the cochlea (Vlajkovic et al, 2009). In the adult cochlea of the rat, ADK immunoreactivity was mostly localized to the nuclear or perinuclear region of spiral ganglion neurons, to lateral wall tissue, and to epithelial cells lining the scala media (Vlajkovic et al, 2010). Like in the brain, ADK expression was subject to highly coordinated expression changes during early postnatal development of the cochlea (Vlajkovic et al, 2010), implicating a putative role of ADK in the regulation of developmental processes.…”
mentioning
confidence: 98%
See 2 more Smart Citations
“…Given the evidence of an otoprotective effect of adenosine described above, restoring adenosine signalling may protect the cochlea from age-related degeneration. Adenosine kinase (ADK) is the primary route for adenosine metabolism and the principal negative regulator of intracellular and extracellular adenosine concentrations in the brain (Boison, 2006) and the cochlea (Vlajkovic et al, 2010b). We have previously demonstrated that physiological reduction of ADK expression is associated with an increase in endogenous adenosine in the brain (Pignataro et al, 2008); conversely, experimental overexpression of ADK in the brain is associated with a reduced concentration of adenosine (Fedele et al, 2005).…”
Section: Introductionmentioning
confidence: 99%